THE INFLUENCE OF SOCIAL MEDIA ACTIVITIES ON BRAND LOYALTY OF KOPI KENANGAN MEDIATED BY INTENTION OF CONTINUED USAGE INTENTIONS - Vionita Qatrunnada; Riski Taufik Hidayah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Social media activities carried out by coffee brands are often used, especially to create loyalty among consumers, but challenges and effectiveness need to be considered to maximize the company's potential. This study aims to determine the brand experience created through social media marketing activities to build brand loyalty. This study will examine social media marketing on the Kopi Kenangan account, sensory brand experience, affective brand experience, behavioral brand experience, intellectual brand experience, value consciousness, brand consciousness, continued usage intention, and brand loyalty, based on the journal by Kumar & Hsieh (2024) titled “How do social media marketing activities affect brand loyalty?” The mediating role of brand experience and Ismail (2017) with the title “The influence of perceived social media marketing activities on brand loyalty: The mediation effect of brand and value consciousness.” The research method used is quantitative, conducting a survey using Google Forms with a sample size of 400 respondents, consisting of Kopi Kenangan consumers who consistently purchase Kopi Kenangan products and recommend Kopi Kenangan products. Descriptive analysis was then conducted based on structural equation modeling and partial least squares data using SmartPLS. The results showed that social media activities influence Kopi Kenangan brand loyalty through brand experience. The results were statistically analyzed using a significance level of 0.05. The researcher found that the calculated t-value was greater than the table t-value (7.577 > 1.65). In other words, social media activities influence brand loyalty. Kopi Kenangan can maximize strategies to enhance brand loyalty through social media activities, which can also serve as a reference for future strategic development.